Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Manajerial Dimoderasi Oleh Leadership dan Budaya Organisasi - Lagasih, Ryna Siskayunita; Tanamal, Cherly Elisabeth (Pascasarjana STIE Amkop Makassar, 2022)
AbstrakThis study aimed to examine the effect of budgetary participation on managerial performance at the Makassar GPIB Education Foundation. To investigate the impact of budgetary participation on managerial performance moderated by leadership and organizational culture at the Makassar GPIB Education Foundation. Data collection techniques were used through observation, questionnaires, and documentation to implement these objectives, with data analysis techniques using moderated regression analysis. The results of the study found that budgetary participation has a positive and significant effect on managerial performance, the interaction of budgetary participation with leadership has a positive and significant impact on managerial performance, and the exchange of budgetary participation with organizational culture has a positive and significant impact on managerial performance at the GPIB Education Foundation Makassar. Kata Kunci: Budaya Organisasi, Leadership, Kinerja Manajerial Dan Partisipasi Penyusunan Anggaran. AbstractFor 150-200 word, An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper. Keywords: Organizational Culture, Leadership, Managerial Performance and Budgeting Participation.